Transformation of views on the essence of the organization's assets in the retrospective and modern period in Russian and foreign literature - V. Manuylenko; M. Galasova (Вестник Северо-Кавказского федерального университета, 2022)
In each period of the country's economic development, the study of the essence and content of the organization's assets is an integral part of corporate financial management. The purpose of the study is to form ideas about the characteristics of the organization's assets based on the study of the transformation of the views of Russian and foreign scientists in the retrospective and modern period. The study examines the characteristics of the concept of «assets» of an economic entity in the temporal aspect – in Ancient Greece, China, Europe, etc., at the turn of the XIX–XX centuries, XX–XXI centuries, modern financial science, the features of their development at each historical stage are determined. A comparison of static and dynamic balance sheet concepts was carried out, which showed that the purpose of the dynamic concept, which reveals the real essence of the company's economic activity, is to determine the financial result, reflect the efficiency of the business entity. As a result, the main approaches to the definition of the concept of "assets of an organization" are identified, including: expenditure-result, subject-material, based on a set of property values, an integral property complex, resource. Their choice depends on the specifics of the activity of the economic entity, the environment of its functioning.